1999
DOI: 10.1086/306893
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Study of the Starburst Galaxy NGC 7714. I. Ultraviolet‐Optical Spectroscopy

Abstract: We have studied the physical conditions in the central 300 pc of the prototypical starburst galaxy NGC 7714. Our analysis is based on ultraviolet spectroscopy with the HST /GHRS and ground-based optical observations, and it also covers X-ray and radio data taken from the literature. The data are interpreted using evolutionary models optimized for young starburst regions. The massive stellar population is derived in a self-consistent way using the continuum and stellar absorption lines in the ultraviolet and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 73 publications
5
25
0
Order By: Relevance
“…In the optical spectrum of their region A (our region 4) 5 SE of the nucleus, they detect Ca II triplet absorption 8600Å features, compatible with two populations, the ionizing population with age ∼5 Myr, and a relatively young RSG-rich population of ∼10 Myr, responsible for the Ca triplet and the Balmer absorption. Further modeling of the UV -NIR spectrum of the nucleus of NGC 7714 (Gonzalez-Delgado et al 1999) found a best fit for a ∼4.5 Myr burst, with upper mass cutoff > 40 M . Gonzalez-Delgado et al (1999) derive a SN rate = 0.007 yr −1 both from the spectral modelling and from radio emission, consistent with the nondetection of SNe in NGC 7714 in the monitoring by Richmond, Filippenko & Galisky (1998).…”
Section: In Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the optical spectrum of their region A (our region 4) 5 SE of the nucleus, they detect Ca II triplet absorption 8600Å features, compatible with two populations, the ionizing population with age ∼5 Myr, and a relatively young RSG-rich population of ∼10 Myr, responsible for the Ca triplet and the Balmer absorption. Further modeling of the UV -NIR spectrum of the nucleus of NGC 7714 (Gonzalez-Delgado et al 1999) found a best fit for a ∼4.5 Myr burst, with upper mass cutoff > 40 M . Gonzalez-Delgado et al (1999) derive a SN rate = 0.007 yr −1 both from the spectral modelling and from radio emission, consistent with the nondetection of SNe in NGC 7714 in the monitoring by Richmond, Filippenko & Galisky (1998).…”
Section: In Amentioning
confidence: 99%
“…Further modeling of the UV -NIR spectrum of the nucleus of NGC 7714 (Gonzalez-Delgado et al 1999) found a best fit for a ∼4.5 Myr burst, with upper mass cutoff > 40 M . Gonzalez-Delgado et al (1999) derive a SN rate = 0.007 yr −1 both from the spectral modelling and from radio emission, consistent with the nondetection of SNe in NGC 7714 in the monitoring by Richmond, Filippenko & Galisky (1998).…”
Section: In Amentioning
confidence: 99%
“…Strong Hα emission indicates a large nuclear H ii region and ongoing star formation (González Delgado et al 1995; Smith, Struck & Pogge 1997). O and B stars are required to fit the UV spectrum, with a best‐fitting age ∼5 Myr and a burst of star formation favoured over continuous star formation (González Delgado et al 1999).…”
Section: Tidal Star‐forming Environments Of Arp 284mentioning
confidence: 99%
“… c Ages determined by photoionization modelling for A, B, C (García‐Vargas et al 1997). Ages for F determined by spectral line synthesis (Gonzáles Delgado et al 1999) and SN rate (Lançon et al 2001). …”
Section: Hst Data Analysismentioning
confidence: 99%
“…The effective Strömgren radius is obtained only at the end of a CLOUDY calculation. The spherical geometry (Stasińska & Leitherer 1996;González-Delgado et al 1999) and plane-parallel geometry (García-Vargas & Díaz 1994;García-Vargas et al 1997) are extreme situations for which the right-hand side of eq. (3) is respectively dominated by the first and the second term.…”
Section: Physical Properties Of the Gasmentioning
confidence: 99%